Controls on accumulation and soil solution partitioning of heavy metals across upland sites in United Kingdom (UK). (15th September 2018) - Zia, Afia; van den Berg, Leon; Ahmad, Muhammad Nauman; Riaz, Muhammad; Zia, Dania; Ashmore, Mike
Abstract: A significant body of knowledge suggests that soil solution pH and dissolved organic carbon (DOC) strongly influence metal concentrations and speciation in porewater, however, these effects vary between different metals. This study investigated the factors influencing soil and soil solution concentrations of copper (Cu), lead (Pb), nickel (Ni) and zinc (Zn) under field conditions in upland soils from UK having a wide range of pH, DOC and organic matter contents. The study primarily focussed on predicting soil and soil solution metal concentrations from the data on total soil metal concentrations (HNO3 extracts) and soil and soil solution properties (pH, DOC and organic matter content). We tested the multiple regression models proposed by Tipping et al. (2003) to predict heavy metal concentrations in soil solutions and the results indicated a better fit (higher R 2 values) in both studies for Pb compared to the Zn and Cu concentrations. Both studies observed consistent negative relationships of metals with pH and loss on ignition (LOI) suggesting an increase in soil solution metal concentrations with increasing acidity. The positive relationship between Pb concentrations in porewater and HNO3 extracts was similar for both studies, however, similar relationships were not found for the Zn and Cu concentrations because of the negative coefficients for these metals in our study. The results of this study conclude that the predictive equations of Tipping et al. (2003) may not be applicable to the field sites where the range of DOC and metal concentrations is much lower than their study. Our study also suggests that the extent to which metals are partitioned into soil solution is lower in soils with a higher organic matter contents due to binding of these metals to soil organic matter. Graphical abstract: Image 1 Highlights: Soil solution concentrations of Cu, Pb, Ni and Zn were studied. Multiparameteric regression models were used to predict metal concentrations. Soil solution metal partitioning and binding varied with DOC concentrations.